Survival and detection of Bacillus cereus in the presence of Escherichia coli, Salmonella enteritidis, Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans after rechallenge in make‐up removers. (14th December 2017) - Yossa, N.; Arce, G.; Smiley, J.; Jo Huang, M.‐C.; Yin, L.; Bell, R.; Tallent, S.; Brown, E.; Hammack, T.
Abstract: Objective: Pathogenic contamination of cosmetics intended to be applied on or around the eye area, including make‐up removers, may lead to severe eye infections. To assess the efficacy of antimicrobial preservatives in these products, we investigated the survival and detection of Bacillus cereus F 4227A spiked into make‐up removers, alone and in the presence of other relevant micro‐organisms. Methods: Four brands of make‐up removers, A, B, C and D, were challenged three times (day 0, day 7 and day 14) using B. cereus, in pure and mixed cultures, at a final concentration of 5 log CFU per mL of Bacillus cereus or 6 log CFU per mL for other micro‐organisms. Inoculated samples were diluted and spiral‐plated after 30 min and 24 h of each challenge onto selective media for recovery of surviving micro‐organisms: BACARA ( B. cereus ), MacConkey ( E. coli ), ChromID ( P. aeruginosa ), XLT4 ( S. enteritidis ), Baird Parker agar ( Staph. aureus ) and PDA+chlortetracycline HCL ( C. albicans ). Results: The population of B. cereus spiked as a pure culture increased significantly from the first to the third challenge after 30‐min exposure time, going from 0.73 to 2.59 in A, from 0.80 to 2.69 in B and from 0.80 to 1.67 log CFU per mL in C ( P < 0.05). Likewise, the B. cereus population from the mixed cultures had a significantly higher survival count at the third challenge: from 0.12 log MPN per mL to 2.16 log CFU per mL in A, 0.57 to 2.27 log CFU per mL in B and from undetected (LOD = 0.48 log MPN) to 0.98 log CFU per mL in C, respectively. After challenges, Staph. aureus, C. albicans and P. aeruginosa increased in B; Staph. aureus and C. albicans in C; and E. coli and Staph . aureus in D. The growth of other bacteria types was unaffected by the number of challenges, but B. cereus population was detected with the third challenge. Conclusion: It is appropriate to assess the antimicrobial efficacy of preservatives using at least three challenges, especially for cosmetics that are subjected to repetitive contamination by users.